Differences in Schools and Opinions of Ulama: Historical Perspectives and Their Functions - Syauqi, Muhammad Hilmi Arif; Nashruddin, Muhammad Rizqi (Ethica: International Journal of Humanities and Social Science Studies, 2024)
The madhhab is the tree of mind or basis used by the mujtahid Imam in solving problems; or abolished Islamic law. The emergence of the madhhab, as part of the historical process of establishing Islamic law neatly arranged from the generation of companions, tabi'in, to reaching the golden age of the Abbasid caliphs, it will be undeniable that the madhhab has contributed great thought in the establishment of Islamic fiqh law. The reasons for the occurrence of differences of opinion / madhab are due to differences in perception in Ushul Fiqh and Fiqh and differences in interpretation or interpretation of mujtahid. Adhering to the idea of madhhab, because of our "inability" factor to explore the sharia law itself directly from its sources (the Qur'an and as-Sunnah). Madhhab correctly can be achieved by understanding that in fact our understanding of differences of opinion among schools is something healthy and natural, the effect of something odd or deviating from Islam.